Legal status of direct sales of agricultural and food products in the legislation of selected EU Member States - Kapała, Anna (Przegląd Prawa Rolnego, 2020)
The purpose of the discussion presented in the article was to determine the legal status of direct sale of agricultural and food products and its place in the agricultural activity in the legislation of selected EU Member States: Poland, Italy, and France. The considerations show that each legislator has chosen a different way of determining the legal status of this activity, though with a view to a similar ratio legis, which is to support it by enabling and facilitating farmers involvement. In Polish law, “agricultural retail sale” is outside the narrow definition of agricultural activity. It is not, however, subject to the provisions of business law provided it meets the conditions specified in law. Italian law defines the status of direct sales explicitly as agricultural, situating them among connected agricultural activities carried out by the agricultural entrepreneur. The detailed criteria for its connection with the agricultural activity by nature constitute a separate special regulation. In French law, thanks to the broad definition of agricultural activity, the place of direct sale as an agricultural activity par relation which is an extension of the act of production, is defined by case-law.